Implementation Of Performance Management In Sarimart Minimarket Branch Bt. 8 Upper - Intan Putri Nurhayati; Laura Atalia; Maya Larasati; Vina Loreza; Satriadi Satriadi (Pusat Riset dan Inovasi Nasional, 2024)
Performance management applications for employees at minimum are a matter of concern. With that the company should always review all the aspects that build up inside the company. Surely the company needs a long-term planning process using performance management. The purpose of this study is to identify the implementation of performance management in employees at the bt branch minimum sarimart.8 tanjungpinang. The research method used in this study is qualitative. The results of this study show how the implementation of performance management at the bt branch sarimart minime.8, peers have implemented performance management through the following process of performance planning, performance planning, training, and guidance, performance assessment and evaluation.